Unbundling Returns to Postsecondary Degrees and Skills: Evidence from Colombia - Matias Busso; Sebastián Monta\~no; Juan S. Mu\~noz-Morales (Institute of Labor Economics (IZA), 2024)
Using longitudinal data of college graduates in Colombia, we estimate labor market returns to postsecondary degrees and to various skills—including literacy, numeracy, foreign language, and field-specific skills. Graduates of academic programs and schools of higher reputation obtain higher earnings relative to vocational public programs. A one standard deviation increase in each skill predicts average earnings increases of one to three percent. Returns vary along the earnings distribution, with tenure, with the degree of job specialization, and by gender. Our results imply that degrees and skills capture different human capital components that are rewarded differently in the labor market.
Keywords: I20; I24; J24; J31; 330; returns to skills; returns to education; numeracy; literacy; foreign language; field-specific; Colombia